A review of MASLD-related hepatocellular carcinoma: progress in pathogenesis, early detection, and therapeutic interventions - Ma, Yang; Wang, Jinguo; Xiao, Wenping; Fan, Xiaoming (Frontiers in Medicine, 2024)
The incidence of metabolic dysfunction-associated steatotic liver disease (MASLD) is continuously rising, evolving into a global health challenge. Concurrently, cases of hepatocellular carcinoma (HCC) associated with MASLD are also on the increase. Although traditional risk factors such as age, gender, and metabolic factors play significant roles in the development of HCC, it cannot be overlooked that MASLD, triggered by changes in modern lifestyle and dietary habits, may also exacerbate the risk of HCC, and this phenomenon is common even among non-obese individuals. Regrettably, MASLD often fails to receive timely diagnosis, resulting in a limited number of patients receiving HCC surveillance.Moreover, there is currently a lack of clear definition for the target population for surveillance beyond patients with cirrhosis. Consequently, MASLD-related HCC is often detected at a late stage, precluding the optimal timing for curative treatment. However, our understanding of the pathogenesis and progression of HCC remains limited. Therefore, this paper reviews relevant literature from recent years, delving into multiple dimensions such as pathogenesis, surveillance and diagnosis, prevention, and treatment, aiming to provide new ideas and directions for the prevention and treatment of MASLD-related HCC.